Международный проект “Зелёное строительство –КНУСА” - Четверіков, Ю. В. (Ways to Improve Construction Efficiency, 2012)
In the article presented the most impotant aspects of Green Building Concepts. The Green Building Concepts means that a building is designed, constructed and renovated according to energy saving principles and environmentaly frendly manner. This aspects are realising in the progect “Green Building – KNUBA”.